Pdgfrα deficiency in islet β-cells up-regulates apoptosis of beta-cells and disturbs glucose metabolism in B6 mice - Zhang, Luyao; Xing, Yanpeng; Wang, Pai; Gu, Jianlei; Peng, Jian; Huang, Juan; Pearson, James Alexander; Hu, Youjia; Zhao, Hongyu; Wong, F. Susan; Wen, Li (Frontiers in Endocrinology, 2025)
IntroductionPancreatic β-cell dysfunction is a key contributor to the development of Type 2 Diabetes. The platelet-derived growth factor receptor α (PDGFRα) is known to play a crucial role in β-cell proliferation and expansion. However, its specific role in β-cell function and glucose metabolism remains unclear. This study aimed to investigate the effects of Pdgfrα deficiency on islet β-cell function and overall glucose metabolism.MethodsTo explore this, we generated β-cell-specific Pdgfrα-deficient C57BL/6 mice (Pdgfrafl/fl Pdx1-cre+) and assessed their metabolic function under both normal and high-fat diet conditions. Various parameters were measured, including body weight, body fat composition, glucose metabolism, insulin content, and β-cell apoptosis. Additionally, we conducted mechanistic analyses to understand the signaling pathways involved.ResultsPdgfrα-deficient mice exhibited significantly greater weight gain and increased body fat compared to controls. These mice also showed impaired glucose metabolism, reduced insulin content in β-cells, and increased β-cell apoptosis. Mechanistic studies revealed that Pdgfrα deletion led to suppression of Atf5 expression via downregulation of the PI3K pathway. This suppression resulted in enhanced β-cell apoptosis. Furthermore, Atf5 was found to regulate the expression of Gadd45b, Bcl2, and aminoacyl-tRNA synthetases, which are involved in insulin biosynthesis and glucose metabolism.DiscussionOur findings demonstrate that PDGFRα plays a critical role in maintaining β-cell function and glucose homeostasis. Loss of PDGFRα impairs β-cell survival and insulin production, likely through the PI3K–Atf5 axis. These insights suggest that targeting β-cell apoptotic pathways, particularly involving Atf5 and its downstream effectors, may offer promising avenues for the prevention and treatment of Type 2 Diabetes.